THE ROLE OF THE TEACHER IN IMPLEMENTING THE 3R-BASED LEARNING MODEL TO THE CREATIVITY SKILLS OF CLASS 1 STUDENTS OF SANGGAR GUIDANCE KEPONG MALAYSIA - Sinaga, Widiana; Nasution, Dewi Kesuma; Syamsuyurnita, Syamsuyurnita; Saragih, Manda (Academy of Education Journal, 2023)
The purpose of this study was to determine the teacher's role in applying the 3R-based learning model to the creativity skills of grade 1 students at the Kepong Malaysia Guidance Studio. This research is a qualitative research. Namely research produces descriptive data in the form of written or spoken words from people whose behavior can be observed. The subject of this research is the principal and teacher. Data collection techniques in this study using observation techniques, interviews and documentation. The results of this study indicate that the role of a teacher in the learning process in the classroom is very important, especially in developing students' creative skills. So in developing creativity skills the teacher must be able to act as a model or example, as a motivator, guide, facilitator and educator, especially in developing the 3R learning model and 3R-based learning methods (reduce, reuse, recycle) Grade 1 students at the Kepong Guidance Center Malaysia in reuse activities namely using a notebook where the paper is still blank and not there for notes or scribbling. Donating clothes that are still usable, and used for rags or mops, in activities to reduce waste, namely using electricity as needed. Bring your own shopping bag to reduce plastic bag waste and process waste into new products. Recycling activities for example: Sorting waste into organic and inorganic waste. Recycle all items that can be recycled, for example plastic, paper, cardboard, glass and cans into pencil cases